Reviving brinjal cultivation in bacterial wilt-prone areas - Choudhary, Anil K; Rahi, Shakuntla (Indian Horticulture, 2015)
The best way to combat this problem is to introduce suitable bacterial wilt resistant cultivars in the region besides proper crop management. Since, Arka Keshav is a bacterial wilt resistant cultivar suitable for wilt-prone areas with high yield potential. Introduction of this bacterial wilt resistant variety has led to revival of brinjal cultivation in the region especially in Balh valley.